Operational Risk Analysis and Solution Implementation in Rizky Strawberry Agrotourism - Sayekti, Ayutyas; Syamsa, Hassa Nur; Hernowo, Jarwadi Budi (Riwayat: Educational Journal of History and Humanities, 2025)
Operational risk management is very important in maintaining the sustainability and success of the agro-tourism business. The research at Rizky Strawberry Sukabumi Agrotourism aims to identify and analyze the operational risks faced and evaluate the effectiveness of the risk management strategies implemented. The methodology uses a descriptive statistical approach and in-depth interviews to internal respondents using questionnaire guidance containing questions related to the implementation of risk management in Rizky Strawberry Agrotourism. The results of the analysis show ten types of operational risks that are grouped based on their causes: human resource risks (human resource competencies, relationships between employees, services, internal controls), system/regulatory risks (safety issues), facilities and infrastructure risks (management of tourist facilities, maintenance, public facilities, technology), environmental risks (pollution), and external risks (natural disasters). Of the ten risks, three are classified as very high, two high, two medium, and three low. The strategy is prioritized to minimize extreme and high risks to medium risk levels.